Changes in Relative Gas Diffusivity Explain Soil Nitrous Oxide Flux Dynamics. Issue 5 (20th September 2013) - Balaine, Nimlesh; Clough, Tim J.; Beare, Mike H.; Thomas, Steve M.; Meenken, Esther D.; Ross, James G.
Abstract : Nitrous oxide (N2 O) is a greenhouse gas and the main anthropogenic emission contributing to stratospheric ozone depletion. Agricultural soils dominate anthropogenic N2 O emissions but there is very limited information specifically relating relative soil gas diffusivity ( Dp/Do ) to N2 O emissions. This study was conducted to determine the effects of soil bulk density (ρ b ) and matric potential (ψ) on Dp/Do and the associated N2 O fluxes in the presence of denitrification substrates. The interaction between soil ρ b and ψ on Dp/Do and N2 O fluxes was investigated using 880 repacked soil cores that were saturated with a nitrate (NO3 – ) solution and placed on tension tables at 11 levels of ψ and 5 levels of soil ρ b . After equilibration (4 d) N2 O fluxes, Dp/Do, inorganic‐N concentrations, and soil physical characteristics were determined. Emissions of N2 O peaked at increasingly lower levels of ψ(–1.5 to –6.0 kPa) as soil ρ b increased (1.1 to 1.5 Mg m –3 ) due to increasing microporosity. Peak N2 O emissions occurred across a relatively wide range of water‐filled pore space (WFPS) and volumetric water content. A Gaussian fit of N2 O‐N fluxes against ψ showed maximum fluxes were related to the soil's air‐entry potential ( r 2 = 0.96). Maximum N2 O emissions occurred at a Dp/Do value of 0.006 that was independent of soil ρ b . Log N2 O‐N flux was a function of log Dp/Do ( r 2 = 0.82) when Dp/Do was >0.006. Soil Dp/Do is a key indicator of N2 O emission potential and needs to be further explored as a predictor of N2 O emissions in a range of soil textures and denitrification substrates.